Kiệt quệ tài chính và quản trị thu nhập: Bằng chứng thực nghiệm ở các công ty niêm yết tại Việt Nam - Lê Thị Phương, Vy (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2020)
This research examines the impact of financial distress on earnings management in Vietnamese listed firms over the 2009-2017 period. The GMM method is used to test this effect. The results show that financial distress is positively related to earnings management. More importantly, different from previous studies, this research investigates the effect of ownership structure as well as firm size and growth rate on this relationship. The regression outcomes point out that foreign ownership, growth rate, and firm size reduce the positive impact of financial distress on earnings management, while the impact of state ownership is not statistically significant.